Development Models for the Brazilian Countryside: Paradigmatic and Territorial Disputes - Fernandes, Bernardo Mancano [UNESP] (Sage Publications Inc, 2016)
Problems of land use and ownership result from the inequalities caused by the hegemonic form of capitalism, agribusiness. A possible alternative model has yet to be worked out, and there is a fundamental need to reflect on the struggle against the hegemony of capitalism and how to safeguard the interests of the peasantry. From this perspective, the agrarian question should be considered as a conflict between those favoring the interests of the peasantry and family farming and those favoring agribusiness. A paradigmatic debate about the roles of the Brazilian state, agribusiness, and the peasant movements in formulating public policy shows that the potential for the peasantry to grow food is threatened by the concentration of power, landownership, capital, technology, and wealth. Unless there is a change in the development model, the prospect is increasing inequality. The experiment with having two government ministries for agriculture is an important step in the shaping of policies to support family farming. Os problemas com uso e propriedade da terra sAo resultados das desigualdades causadas pelo modelo capitalista hegemonico denominado agronegocio. Um possivel modelo alternativo esta sendo gestado e ha necessidade de refletir sobre a luta contra a hegemonia do capitalismo e como salvaguardar os interesses dos camponeses. A partir desta perspectiva, a questAo agraria deve ser considerada como conflitualidade permanente entre os interesses dos camponeses ou agricultura familiar e os interesses do agronegocio. O debate paradigmatico contribui para compreender o papel do Estado brasileiro, do agronegocio e dos movimentos camponeses na formulacAo de politicas publicas. Tambem mostra que as possibilidades de criacAo de um modelo de desenvolvimento do campesinato esta ameacado pela concentracAo de poder, propriedade da terra, capital, tecnologia e riqueza nas mAos do agronegocio. Se nAo houver uma mudanca com a criacAo de um modelo de desenvolvimento voltado aos interesses da agricultura camponesa, a perspectiva e de aumento da desigualdade. A experiencia de ter dois ministerios para a agricultura e condicAo fundamental na definicAo de politicas de apoio a agricultura camponesa e familiar.
Keywords: Peasantry; Agribusiness; Paradigm; Territory; Development